An ontological approach to describing neurons and their relationships - Hamilton, David J.; Shepherd, Gordon M.; Martone, Maryann E.; Ascoli, Giorgio A. (Frontiers in Neuroinformatics, 2012)
The advancement of neuroscience, perhaps the most information rich discipline of all the life sciences, requires basic frameworks for organizing the vast amounts of data generated by the research community to promote novel insights and integrated understanding. Since Cajal, the neuron remains a fundamental unit of the nervous system, yet even with the explosion of information technology, we still have few comprehensive or systematic strategies for aggregating cell-level knowledge. Progress toward this goal is hampered by the multiplicity of names for cells and by lack of a consensus on the criteria for defining neuron types. However, through umbrella projects like the Neuroscience Information Framework and the International Neuroinformatics Coordinating Facility, we have the opportunity to propose and implement an informatics infrastructure for establishing common tools and approaches to describe neurons through a standard terminology for nerve cells and a database (a Neuron Registry) where these descriptions can be deposited and compared. This article provides an overview of the problem and outlines a solution approach utilizing ontological characterizations.